2007
DOI: 10.1002/polb.21114
|View full text |Cite
|
Sign up to set email alerts
|

Conductive ATO‐acrylate nanocomposite hybrid coatings: Experimental results and modeling

Abstract: The electrical volume conductivity r of antimony-doped tin oxide (ATO)-acrylate nanocomposite hybrid coatings was investigated. The relation between r and the volume filler fraction p was analyzed for the ATO-acrylate coatings containing ATO nanoparticles grafted with different amounts of 3-methacryloxy-propyl-trimethoxy-silane coupling agent. Percolation thresholds were observed at very low filler fractions (1-2 vol %) for the coatings containing ATO nanoparticles with a low amount of surface grafting. A modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…To be certain that these particles are well dispersed in the acrylate monomer before and during irradiation the surfaces of these particles are grafted with MPS. It is well-known that this methacrylate surface modification prevents the agglomeration of the Sb:SnO 2 (Sb ≥ 0%) nanoparticles in the monomer mixture before and during the curing of the acrylate matrix and that even at low particle concentration particle networks are formed during cure ( Figure 1) [1,4,28].…”
Section: Measurement Of the Absorption Spectra Of The Sb:snomentioning
confidence: 99%
See 2 more Smart Citations
“…To be certain that these particles are well dispersed in the acrylate monomer before and during irradiation the surfaces of these particles are grafted with MPS. It is well-known that this methacrylate surface modification prevents the agglomeration of the Sb:SnO 2 (Sb ≥ 0%) nanoparticles in the monomer mixture before and during the curing of the acrylate matrix and that even at low particle concentration particle networks are formed during cure ( Figure 1) [1,4,28].…”
Section: Measurement Of the Absorption Spectra Of The Sb:snomentioning
confidence: 99%
“…Spherical nanoparticles of antimony-doped tin oxide (Sb: SnO 2 ) can be used to provide semiconducting properties to insulating polymers. This change in properties occurs when these particles form a percolating network structure through the polymer matrix [1][2][3][4][5][6] at a filler concentration higher than the percolation threshold. In a number of scouting experiments in which we studied the rate of curing of such Sb:SnO 2 )/acrylate formulations, we noticed that in the absence of an organic photoinitiator UV curing also occurred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in general, starting formulations containing MPS grafted Sb : SnO 2 particles were used. The amount of methacrylate (MPS) moieties grafted on the surface of our Sb : SnO 2 particles surface and the amount of methacrylate (MPS) oligomer present in the starting formulation depend on the MPS/Sb : SnO 2 ratio used in the grafting reaction (Schemes 2 and 3) [2,12,22,25]. It has been shown that these amounts are hardly influenced by the surface and bulk composition of our Sb : SnO 2 nanoparticles (Scheme 3).…”
Section: Influence Of Mps Grafting and Mps Oligomersmentioning
confidence: 99%
“…Hence, in this work well-characterized Sb : SnO 2 nanoparticles of varying composition, but with similar nanoparticle sizes and crystallinities, are used (Table 1). To be certain that these particles are well dispersed before and during irradiation in the acrylate monomer their surfaces were grafted in advance with MPS [13,14,25]. PEGDA 575 was chosen as acrylate monomer to minimize the influence of viscosity variations on the rate of the acrylate polymerization during irradiation.…”
Section: Quantum Yields At Different Wavelengths Of Irradiationmentioning
confidence: 99%